(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2004)
Starting with the vision of Aristotle that the man was a politician animal, that the social sciences aim to explore and to find solutions for the human being coexistence, the author goes to the origin of the Federalism and to the Federal State.